[Media industry : trade catalogues ephemera collected by the National Library of Australia]
Material in the trade catalogues ephemera collection covers significant information on Australian companies, businesses, industries, manufacturers, retailers and trades, describing their services and products. This promotional literature includes catalogues, advertisements, announcements, brochures, calendars, cards, coupons, directories, flyers, handbills, labels, notices, novelty advertising, pamphlets, price lists, tokens.
Keywords: Advertising -- Brand name products -- Australia; Advertising -- Australia -- Miscellanea; Business -- Australia -- Miscellanea; Commercial catalogs -- Australia; Industries -- Australia -- Miscellanea; Retail trade -- Australia -- Miscellanea; Trade literature -- Australia; Australia -- Commerce -- Miscellanea; Media industry; Newspapers; Television services